Bilateral decompression using a unilateral pedicle construct for lumbar stenosis - Mao, Lu (Springer Berlin Heidelberg, 2013)
PURPOSE: To determine the effectiveness of bilateral decompression via a unilateral approach using unilateral pedicle screw fixation for two-level lumbar stenosis with instability. METHODS: Between October 2006 and October 2010, 98 patients (61 men and 37 women) who had reached the three-year follow-up interval were treated with unilateral pedicle screw fixation at the authors’ institution. All patients underwent two-level transforaminal lumbar interbody fusion (TLIF), and the mean age was 59.6 years (range, 40–72). Visual analog scale (VAS) scores and Oswestry Disability Index (ODI) were used to assess the pre-operative and postoperative clinical results. Fusion status, the disc space height, and the whole lumbar lordotic angle were analysed for the radiological evaluation. RESULTS: The ODI scores decreased significantly in both early and late follow-up evaluations and the visual analog scale (VAS) score demonstrated significant improvement in late follow-up (P < 0.01). The disc space height (P < 0.05) and the whole lumbar lordotic angle (P < 0.05) were increased at the final follow-up. Successful fusion was achieved in all patients. CONCLUSION: Bilateral decompression via a unilateral approach using unilateral pedicle screw fixation for two-level lumbar stenosis with instability, which can maintain the lumbar lordosis and the disc space height, is an effective and less invasive method than with bilateral constructs.